Analisis Sosial Ekonomi Dan Produktivitas Usaha Tambak Udang Bapak Johan Di Kecamatan Pondok Kelapa Kabupaten Bengkulu Tengah - Zaky Apriadi; Herri Fariadi; Evi Andriani (Jurnal Multidisiplin Dehasen (MUDE), 2026)
The purpose of this study is to analyze the socioeconomic conditions of shrimp farming in Mr. Johan's shrimp farming business in Pondok Kelapa Subdistrict, Central Bengkulu Regency, and to determine the productivity of shrimp farming in Mr. Johan's shrimp farm in Pondok Kelapa Subdistrict, Central Bengkulu Regency. The research method used was descriptive qualitative. The results of the study reveal that this shrimp farming business has had a significant economic impact on both the farm owner and the surrounding community. Mr. Johan's shrimp farming business in Central Bengkulu involves the local community as laborers, which has changed their livelihood from agriculture to shrimp farming. There are no land conflicts due to mutual agreement, and the existence of the farm has increased the income and economic welfare of the surrounding community. Waste management is carried out properly so that the environmental impact can be minimized, and Mr. Johan's shrimp farming business shows quite good performance with high efficiency and production yields. With an area of 6 hectares, the farm is capable of producing around 50 tons of shrimp per harvest, or the equivalent of 8,333 kg per hectare per harvest. If two harvests are carried out in one year, the total annual productivity reaches 16,666 kg per hectare per year.